PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XII MIA SMA NEGERI 2 BAYANG - Utami, Windi Kartika (Departemen Matematika, 2023)
Understanding maths is essential for students. However, class XII MIA SMA Negeri 2 Bayang pupils' mathematics knowledge is low since the learning model has not supported it. The Two Stay Two Stray (TSTS) model is used to solve this problem. Descriptive and quasi-experimental research with non-equivalent posttest-only control group design is used. The population was 2023/2024 SMA Negeri 2 Bayang class XII students. For sampling, researchers utilised simple random sampling. Experimental class was XII MIA 1 and control class was XII MIA 2. Quizzes and final maths tests were used for research. The hypothesis test of the last test of knowing concepts systematically yielded a P-value of 0.019, rejecting H0. In class XII MIA SMA Negeri 2 Bayang, students who learn with Two Stay Two Stray (TSTS) grasp mathematical concepts better than those who learn directly.Keywords - Two Stay Two Stray (TSTS) Cooperative Learning Model, Understanding Mathematical Concepts, Direct Learning.